Estimasi Biaya Ekonomi Pembangunan Pariwisata Berbasis Sungai di Provinsi Kalimantan Selatan - Muhammad Abigail Faza (PARAHYANGAN ECONOMIC DEVELOPMENT REVIEW, 2022)
South Kalimantan Province is one of the provinces that has the largest number of rivers; namely, there are 58 rivers. The river has a strategic role for the people of South Kalimantan as a natural resource that can support various activities. Watershed management is intended as an effort to plan and evaluate the conservation of river resources. Using rivers, including tourism, can have a multiplier effect on the regional economy. Therefore, this study aims to determine whether every river in South Kalimantan can become a tourism destination and to calculate the economic costs arising from river-based tourism development activities. In this study using, the research method is economic valuation. The research calculations show that the total private costs are Rp. 118,423,429,388 divided from operational costs of Rp. 25,881,210,800 and a construction cost of Rp. 92,542,218,588. While the social costs of Rp. 15,235,806,143,180.